A New Upper Limit on Graviton Mass from Large-Scale Gravitational Convergence Analysis - Goshu, Belay Sitotaw (Britain International of Exact Sciences (BIoEx) Journal, 2024)
This study investigates the limits on graviton mass using a convergence-based approach within the framework of gravitational physics. By employing theoretical models and computational simulations, we derive a graviton mass limit that is then compared with existing constraints from astrophysical observations and quantum field theories. The findings suggest that the mass of the graviton, although typically assumed to be negligible, can be constrained through gravitational wave dynamics and the interactions of massive bodies in the universe. The results highlight the potential for significant implications in our understanding of gravitational interactions and encourage further interdisciplinary research to explore the nature of gravity at both cosmological and quantum scales. These insights may pave the way for future investigations in gravitational wave astronomy, contributing to our understanding of fundamental forces in the universe.